Strategic trade policy for Eastern Europe - Franz Peter Lang (Intereconomics, 1992)
The integration of the former state-trading countries into international free trade may, on the one hand, sensibly complement the reforms now under way towards their becoming market economies; on the other hand, this move harbours the risk of perpetuating and indeed aggravating the economic backwardness of those countries. The detrimental effects can be avoided if a product-cycle-oriented economic policy is pursued which makes a deliberate point of utilizing the relatively rich endowment of human capital available in these countries.
Keywords: 330; System Transformation